Pengaruh Servant Leadership dan Intrinsic Motivation Terhadap Kinerja Guru di SDN 174 Pasir Impun Kota Bandung - Aquilla, Felicia; Rahayu, Muji (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This research aims to examine the influence of servant leadership and intrinsic motivation on teacher performance at SDN 174 Pasir Impun, Bandung City. Saturated samples, or all members of the population sampled, are used in the sample computing approach. Overall, 46 people participated in the poll. The data collection technique uses a questionnaire. Descriptive and verification analysis are included in quantitative research techniques. The results of the hypothesis test show that the influence of servant leadership and intrinsic motivation has a significant and positive effect on performance. This shows how effective performance can be achieved at a high level of servant leadership and intrinsic motivation.